Neutral atom quantum computing hardware: performance and end-user perspective - Wintersperger, Karen; Dommert, Florian; Ehmer, Thomas; Hoursanov, Andrey; Klepsch, Johannes; Mauerer, Wolfgang; Reuber, Georg; Strohm, Thomas; Yin, Ming; Luber, Sebastian (EPJ quantum technology, 2023)
We present an industrial end-user perspective on the current state of quantum computing hardware for one specific technological approach, the neutral atom platform. Our aim is to assist developers in understanding the impact of the specific properties of these devices on the effectiveness of algorithm execution. Based on discussions with different vendors and recent literature, we discuss the performance data of the neutral atom platform. Specifically, we focus on the physical qubit architecture, which affects state preparation, qubit-to-qubit connectivity, gate fidelities, native gate instruction set, and individual qubit stability. These factors determine both the quantum-part execution time and the end-to-end wall clock time relevant for end-users, but also the ability to perform fault-tolerant quantum computation in the future. We end with an overview of which applications have been shown to be well suited for the peculiar properties of neutral atom-based quantum computers.